Some Thoughts on "Travestis", Clients and Husbands: Gender and Sexuality in The Construction of the Identities of Brazilian Travesti Sex Workers - Vartabedian Cabral, Julieta (Revista de Antropología Social, 2024)
This article examines the way Brazilian travesti sex workers interact socially and sexually with their clients and husbands in order to build their identities as travestis. Travestis, who are not cross-dressers nor transsexuals, constitute a kind of gender identity that not only emphasizes how gender is done, but at the same time decentralizes how bodies become “legible”. Travestis embody an ideal and fictional type of woman and, simultaneously, make use of a considered typically male sexuality. On the basis of one of the ways in which sexuality is organized in Brazil —“active/passive” model—, a hierarchical relationship is established between, on the one hand, those who are considered to be “real men” and, on the other hand, those who are feminized, devalued and stigmatized for being dominated sexually. Paradoxically, travestis pass fluently between both margins of sexuality and gender. This article highlights that it is important to distinguish how gender roles are acted and interpreted in order to understand the sexual practices of travestis and to make sense of how they construct their own way of understanding femininity.
Keywords: Gender; Sexuality; Travestis; Sex Work; Clients; Husbands; “Active/Passive” Model; Masculine/Feminine; Rio de Janeiro; Barcelona.